The Influence of Board Size and Ethnic Diversity in Share Repurchases Policy - Rohaida Abdul Latif; Kamarun Nisham Taufil Mohammed; Hasnah Kamardin (International Review of Management and Marketing, 2016)
This study examines the efficacy of the recent amendment in Malaysian Code on Corporate Governance 2012 in curbing the likelihood of earnings management in share repurchases policy in Malaysia. Based on 275 firm-year observations among share repurchasing firms between 2006 and 2010, we find that by frequently repurchases shares, companies are able to manage their earnings upwards. It is also found that ethnic diversity can help curb the potential misuse of managerial discretion in deciding whether to frequently repurchase shares. Our study contributes to the existing literature on board characteristics in several ways. First, it provides evidence that board diversity in terms of ethnicity can significantly affect companies’ policy. We find that companies with less diverse board as measured by ethnic group are more likely to frequently embark on share repurchase to seemingly improve current earnings. Second, we find that large board size can significantly reduce the tendency of managerial opportunistic behaviour. The study provides early evidence of the effectiveness of recent Malaysian code on corporate governance 2012 which recommended diverse balance of board members to ensure proper monitoring role and curbing the likelihood of unwarranted managerial opportunistic behaviour by unduly controlling owners.